O que é ser bilíngue? Na percepção de professores de escolas bilíngues - Fernandes, Rafaela (2016)
In light of English as a global language and on the face of its teaching and learning expansion worldwide, specially in Brazil, this study aims to conduct an overall review of the theories about the bilingualism concept and bilingual education. Moreover, this work also seeks to analyze the bilingual school teacher perceptions about the concept of bilingualism and stablishes points of convergence and divergence among their perspectives, the school pedagogical proposal and the existing literature on the subject. This study was developed based on desk and qualitative research enabled by a collection of data on the bilingual school teachers perceptions about bilingualism.